IMF Survey, Volume 36 Issue 08. (IMF Survey; IMF Survey, 2007)
De Rato on hedge funds and trade; Portugal on IMF technical assistance; Latin American growth; Iraq reforms economy; debt restructuring in eight countries; IMF research: investment, reserves, inflation; exchange rate adjustment and global imbalances.